Marginally hydrogenated triphasic titania nanotubes for effective visible-light photocatalytic hydrogen generation - Preethi, Laguduva K.; Mathews, Tom; Walczak, Lukasz; Gopinath, Chinnakonda S. (Energy Technology, 2018)
We report the first demonstration of hydrogen-annealed triphase TiO nanotubes (anatase-rutile-brookite) (T-ARB) as a visible-light-active photocatalyst for water splitting with high quantum efficiency. As-synthesized T-ARB was annealed under hydrogen atmosphere at 250 and 4508 degrees C for 2 h. We found that the tubular structures were retained in the hydrogenated TiO2 samples. It was observed that the concentrations of Ti3+ and the oxygen vacancies and their distribution significantly increased with respect to the hydrogen annealing temperature. Such changes in defects were found to be critical in enhancing the photocatalytic activity of the hydrogen-annealed triphase TiO2 nanotubes. The triphase TiO2 nanotubes hydrogen annealed at 450 degrees C were 16 times more efficient than pristine TiO2. Such an increase in the photocatalytic activity was explained by a triphase band diagram with defect states below the conduction band of each phase, which facilitated visible-light activity and easy transfer of charge carriers from one phase to another. Our study showed that the well-designed multiphase construction with oxygen vacancies enhanced the photocatalytic activity tremendously owing to the presence of a higher number of phase junctions.
Keywords: charge transfer; Defects; Hydrogenation; titania; water splitting